Dissolution behaviour of different rank coals in L‐glutamic acid N, N‐diacetic acid chelating agent: Implications to enhance coalbed methane recovery by acid stimulation. (15th December 2021) - Chen, Shuya; Yang, Xianyu; Shi, Yanping; Wei, Zhaohui; Zhang, Jie; Cai, Jihua
Abstract: Acid stimulation is a promising method in improving coal seam permeability by demineralization in coal cleats. However, using conventional acids such as HCl and mud acid (12 wt.% HCl + 3 wt.% HF) may cause clay breakage, migration, and precipitation, leading to formation damage. In this study, we investigated the effect of L‐glutamic acid N, N‐diacetic acid (GLDA) chelating agent treatment on the dissolution behaviour of lignite (Coal L) and anthracite (Coal A), collected from Er′Lian Basin and Qinshui Basin, China. Characteristics of the raw and acid treated coal samples, including mercury intrusion porosimetry (MIP) results as well as metal elements distribution analysis of reacted leachates, micromorphology, mineral composition, and mass change were taken into consideration. It was found that high‐rank Coal A is more suitable for chemical stimulation. For both Coal L and Coal A, 5 wt.% GLDA solution is preferred to avoid sticking reaction products. Total porosities of Coal L and Coal A were increased by 3.9 and 1.1 times, respectively. Based on the water chemistry analysis of the reacted solutions, we found that acidic condition is beneficial for clay minerals and carbonates dissolution, while alkaline condition is favourable for the dissolution of quartz. Besides, the dissolution of minerals can trigger the release of trace elements, which is a potential environmental risk that needs to be taken into consideration before its in‐situ application in coal fields.